Sustainable energy storage in the scope of circular economy : advanced materials and device design - Costa, Carlos Miguel, 1991-; Gonçalves, Renato; Lanceros-Méndez, Senentxu, 1968- (John Wiley & Sons, Inc., 2023)
"In the context of the EU Action Plan for the Circular Economy, and the United Nations 2030 Agenda for Sustainable Development, the development of smart and multifunctional composites based on sustainable materials are essential for a significant number of application areas. One of the most important areas is energy storage devices. This book reviews the recent developments in energy storage devices based on sustainable materials, within the framework of the circular economy. The sustainable design and application of energy storage devices is addressed, with consideration of the key advantages and remaining challenges in thisrapidly evolving research field. Topics covered include: ? Production processes for batteries based on bioeconomy ? Sustainable materials for batteries ? Sustainable materials for supercapacitor devices ? Sustainable materials for fuel cells devices ? Multifunctional sustainable materials for energy storage ? Sustainable energy storage devices and device design for sensors and actuators, biomedical applications, wearables, electric vehicles ? Energy storage devices in the scope of the Internet of Things ? Waste prevention for energy storage devices based on second life ? Recycling procedures for energy storage devices"--